219 Relationship between host-genetics and the vaginal microbiome in commercial gilts. (5th December 2019) - Sanglard, Leticia; Schmitz-Esser, Stephan; Gray, Kent; Linhares, Daniel C L; Yeoman, Carl J; Dekkers, Jack C; Niederwerder, Megan C; Serão, Nick V
Abstract: The objective of this study was to investigate host-genetic contributions to the vaginal microbiome of commercial gilts vaccinated for Porcine Reproductive and Respiratory Syndrome (PRRS). Vaginal swab samples (n = 576) from 308 F1 gilts (183±12 days old) were collected on day 4 (D4) and 52 (D52) post-vaccination with a commercial modified live virus PRRS vaccine. Samples were used to profile the vaginal microbiome by 16S rRNA gene sequencing, with sequences clustered into operational taxonomic units (OTUs) and taxonomically classified. All animals were genotyped for 45, 536 SNPs. Arcsine of the square root-transformed OTUs abundance data were analyzed using a linear mixed animal model with age at vaccination as a covariate and animal (random) for estimation of genetic parameters. The same model was used for GWAS for the 100 most abundant OTUs but with addition of genotype of SNPs as a covariate, one at a time. For D4, heritability estimates ranged from < 0.001±0.01(13 OTUs) to 0.60±0.13 (Fusobacterium), with OTUs corresponding to the genera Fusobacterium, Pasteurellaceae, Clostridiales, Prevotellaceae, and Lactobacillus having high estimates (0.41±0.13 to 0.60±0.13). For D52, heritability estimates ranged from < 0.001±0.01 (10 OTUs) to 0.63±0.12 (Terrisporobacter), with OTUs corresponding to Clostridium, Terrisporobacter, Romboutsia, Turicibacter, Phascolarctobacterium, Muribaculaceae, and Ruminococcaceae having high estimates (0.42±0.14 to 0.63±0.12). Forty-six QTLs were significantly (P < 0.00001) associated with OTU across days. Among these, one main QTL on chromosome 12 (20–23Mb), a gene-rich region with previously identified QTL for immune-related traits, was identified for 5 and 6 OTUs on D4 and D52, respectively. These OTUs were mainly of the phyla Proteobacteria and Firmicutes on D4 and D52, respectively. In conclusion, there is evidence of substantial host genetic variation for vaginal microbiome in commercial PRRS-vaccinated gilts, including the identification of many QTLs. Additional research is needed to investigate the genetic relationship between vaginal microbiome, health, and production in pigs.